The Evolution of Competitive Intelligence - Prescott, John E. (Journal of Sustainable Competitive Intelligence, 2012)
DESIGNING A PROCESS FOR ACTION The purpose of a competitive intelligence (CI) program is to develop action-oriented implications for managers. This is an overview of the evolution of competitive intelligence and of the fundamental concepts of CI, including the intelligence production process. Effective CI is critical in helping the proposal management professional create competitive responses to RFPs and commercial opportunities. Clique Aqui Fonte: Association of Proposal Management Profissional (APMP) . Proposal Management, p. 37-52